2009
DOI: 10.1007/s11258-009-9618-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal litterfall heterogeneity generated by woody species in the Central Monte desert

Abstract: In arid and semiarid environments, the presence of woody species generates a series of environmental gradients that increase spatial heterogeneity and modify the pattern of distribution of the other species. We postulate that the temporal and spatial variability in litter input generated by woody species is a relevant factor in the generation of edaphic heterogeneity by redistribution of nutrients and the physical effects of litter. The objective of this study was to determine the temporal and spatial variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
9
25
1
3
Order By: Relevance
“…Our findings showed that the inter-and intraannual patterns of leaf litterfall in most species varied with precipitation in accordance to other studies carried out both in forests (Münster-Swendsen 1984;Bo Pedersen and Bille-Hansen 1999) and deserts (Strojan et al 1979;Maya and Arriaga 1996;Sala et al 1988;Lauenroth and Sala 1992;Alvarez et al 2009). These studies argued that mean annual precipitation accounts for most of the net primary aboveground production variability and consequently for the interannual variability in leaf litter production.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings showed that the inter-and intraannual patterns of leaf litterfall in most species varied with precipitation in accordance to other studies carried out both in forests (Münster-Swendsen 1984;Bo Pedersen and Bille-Hansen 1999) and deserts (Strojan et al 1979;Maya and Arriaga 1996;Sala et al 1988;Lauenroth and Sala 1992;Alvarez et al 2009). These studies argued that mean annual precipitation accounts for most of the net primary aboveground production variability and consequently for the interannual variability in leaf litter production.…”
Section: Discussionsupporting
confidence: 93%
“…Probably, large precipitation events in winter could provoke the mechanical shedding of senesced leaves. A recent study in the Central Monte Desert stood out the role of rainfall as a turnover control of plant parts (Alvarez et al 2009). Lastly, perennial grasses did not show a clear seasonal leaf litterfall pattern probably due to leaves remained attached to the bunch for long periods (Soriano 1956).…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive structure fraction is directly related to the type of climate and to the phenologies of the dominant species (Lampe et al, 1992;Diniz and Pagano, 1997;Martínez-Yrízar et al, 1999;Alvarez et al, 2009). According to Amorim et al (2009), wide variations in the flowering patterns of caatinga species have been noted, influencing the spatial patterns of reproductive structure productions.…”
Section: Discussionmentioning
confidence: 99%
“…7). This should be related to the relatively high woody vegetation cover of the valley, the dominance of P. flexuosa trees (Alvarez et al 2009), and the accessibility to the water table that should promote P. flexuosa and other species growth, leaf and litter production, and overall valley productivity. Although there are not previous reports on the growth rate of P. flexuosa trees from valleys and dunes in the Monte Desert, some preliminary data suggest a greater leaf expansion in trees from the valley than trees from the dune even during an exceptional rainy year (unpublished data).…”
Section: Discussionmentioning
confidence: 99%